Dopaminergic system and addiction - Şengül, Cem; Herken, Hasan (Journal of Dependence, 2009)
Dopamine is a common neurotransmitter in central nervous system. Researchers were reporting that dopamine plays an important role in the development and persistence of addiction. Most important contribution revealing the association of dopaminergic system with addiction comes from brain imaging studies and pharmacological researches. These studies were mentioning that dopaminergic system was involved in the development and persistence of addiction by effecting brain reward system, craving and cognitive processes. Association of dopaminergic system and addiction was also investigated by genetic and epigenetic studies. In this paper we aimed to review the association of dopaminergic system with addiction.
Keywords: Addiction; dopamine; genetic; neurobiology